2016
DOI: 10.1177/0300060515625431
|View full text |Cite
|
Sign up to set email alerts
|

A survey of subcutaneous blood flow in patients with SMID and subcutaneous ceftazidime administration using mentholated warm compresses in healthy subjects

Abstract: ObjectivesTo investigate subcutaneous blood flow rate (SBFR) in healthy volunteers and patients with severe motor and intellectual disabilities (SMID), and evaluate the effect of mentholated warm compresses (MWCs) on SBFR and subcutaneous ceftazidime absorption in healthy volunteers.MethodsSBFR at the forearm, chest and abdomen were evaluated in Japanese healthy volunteers and in adults with SMID. The effects of MWCs on blood flow rate and ceftazidime pharmacokinetics were evaluated in healthy volunteers.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, it must be reminded that the subcutaneous administration of cephalosporin is potentially harmful, as published in a recent study on ceftriaxone [10]. A study, performed among healthy subjects (n = 18) and subjects with severe motor intellectual disabilities (n = 29), showed that subcutaneous ceftazidime bioavailability increased with the use of mentholated warm compresses (i.e., by increasing blood flow rate) [11]. The time to complete systemic diffusion of ceftazidime was 120 min with mentholated warm compresses vs. 205 min without, and the maximum ceftazidime plasma concentration was 57.4 lg/mL vs. 44.8 lg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be reminded that the subcutaneous administration of cephalosporin is potentially harmful, as published in a recent study on ceftriaxone [10]. A study, performed among healthy subjects (n = 18) and subjects with severe motor intellectual disabilities (n = 29), showed that subcutaneous ceftazidime bioavailability increased with the use of mentholated warm compresses (i.e., by increasing blood flow rate) [11]. The time to complete systemic diffusion of ceftazidime was 120 min with mentholated warm compresses vs. 205 min without, and the maximum ceftazidime plasma concentration was 57.4 lg/mL vs. 44.8 lg/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…infusion. However the area under the concentration-time curve (AUC), the minimum blood concentration (C min ) and the t 1/2 was comparable between the two different administration routes [5][6][7][8].…”
Section: Cephalosporinsmentioning
confidence: 99%
“…Some authors attempted to enhance the absorption of cephalosporins through s.c. administration by using some agents that increase connective tissue permeability, such as hyaluronidase, or the subcutaneous blood flow rate (such as mentholated warm compresses) [6,7]. These strategies appeared to exert a favorable influence on cephalosporin C max and T max when administered subcutaneously.…”
Section: Cephalosporinsmentioning
confidence: 99%
“…68e71 Also, interestingly, simple tools like mentholated warm compresses, may improve the SC blood flow rate and absorption of antibiotics. 50 The SC route may be a useful resource in the treatment of ambulatory patients in developing countries, as well as vulnerable patients (including IV drug users), people in remote locations, and in finding applications in military medicine.…”
Section: Future Perspectives Regarding Sc Administrationmentioning
confidence: 99%